Export Promotion A Decision Support Model Approach - Cuyvers, Ludo (African Sun Media, 2012)
Governments are increasingly confronted with scarce resources, which force their export promotion organisations to seek more efficient ways and methods. At the same time, with the export successes of the emerging economies, public export promotion policies of countries are confronted with diminishing returns, particularly when the traditional export promotion instruments are used. The DSM (Decision Support Model) approach to export promotion, which is adopted and explained in the book, is deeply rooted in the international marketing research literature and allows to identify, in the rapidly changing international environment, the most promising realistic export opportunities for exporting countries.